Synchrotron X-Ray Radiation-Induced Bystander Effect: An Impact of the Scattered Radiation, Distance From the Irradiated Site and p53 Cell Status - Lobachevsky, Pavel; Forrester, Helen B.; Ivashkevich, Alesia; Mason, Joel; Stevenson, Andrew W.; Hall, Chris J.; Sprung, Carl N.; Djonov, Valentin G.; Martin, Olga A. (Frontiers in Oncology, 2021)
Cancer radiotherapy is based on the dogma that radiation kills targeted cells. The radiation-induced bystander effect (RIBE), by which the neighbours of irradiated cells can also be damaged, challenges this dogma. RIBE is now a well-established consequence of ionizing radiation and is manifested as increased genomic abnormalities and loss of viability of the ‘naïve’ cells. Therefore, RIBE represents a risk factor in radiotherapy that needs to be considered, including for treatment with novel radiotherapy modalities, such as synchrotron-generated microbeam radiotherapy (MRT). Here, we quantitatively assessed the contribution of scattered synchrotron radiation to the observed RIBE, manifested as DNA damage in cultured human colon cancer cells, for both a collimated MRT beam and a broad beam (homogeneous) control. We report that scattered radiation substantially contributes to DNA damage accumulation in bystander cells, and that the cells exposed to the low-dose scatter generate unrepairable DNA damage, possibly due to an ongoing exchange of bystander signalling. We found a more pronounced bystander response following irradiation with broad beam compared to MRT. For p53-null cells, we describe an overall reduced response to low-dose irradiation, but not for RIBE. Our findings provide new information for optimization and planning of cancer MRT regimens.